Comparison of methods for determining the partition coefficient of gadolinium in the myocardium using T1 mapping. Issue 1 (29th November 2012) - Salerno, Michael; Janardhanan, Rajesh; Jiji, Ronny S.; Brooks, Jeremy; Adenaw, Nebiyu; Mehta, Bhairav; Yang, Yang; Antkowiak, Patrick; Kramer, Christopher M.; Epstein, Frederick H.
<x xml:space="preserve">Abstract</x> Purpose To develop and validate modified Look‐Locker (MOLLI) protocols to generate myocardial T1 maps within clinically acceptable breath‐hold durations and to compare partition coefficients (λ) of gadolinium (Gd)‐DTPA determined from either bolus injection (BI) or continuous infusion (CI) techniques. Materials and Methods T1 mapping was performed in phantoms and in 10 volunteers on a 1.5T scanner using the standard (3‐3‐5) MOLLI technique and two MOLLI schemes with shorter breath‐hold durations. Imaging was performed precontrast and every 5 minutes following a bolus of 0.1 mmol/kg Gd‐DTPA and a 15‐minute delayed continuous infusion of 0.001 mmol/kg Gd‐DTPA until equilibrium T1 in the myocardium was achieved to enable direct comparison of T1 relaxation times between techniques and λ's between the BI and CI methods. Results There was good agreement of T1 values between the 3‐3‐5 standard MOLLI protocol and the modified 3‐5 MOLLI protocol in both phantom studies over a range of heart rates and in human subjects. Both MOLLI protocols produced similar measurements of λ using both the BI and CI methods. Conclusion A reduced breath‐hold MOLLI T1 mapping protocol combined with the BI method can accurately characterize T1 and λ in clinically applicable breath‐hold durations without requiring a long equilibrium phase infusion. J. Magn. Reson. Imaging 2013;38:217–224. © 2012 Wiley Periodicals, Inc.